Moral judgment competence of medical students: a transcultural study - Neves Feitosa, Helvécio; Rego, Sergio; Unger Raphael Bataglia, Patricia [UNESP]; Castelo Branco Sancho, Karlos Frederico; Rego, Guilhermina; Nunes, Rui (Springer Nature, 2013)
The authors conducted a cross-sectional short-term study using Lind's Moral Judgment Test (MJT) to compare moral judgment competence (C-score) among students from a medical school in the Northeast region of Brazil and a medical school in the Northern region of Portugal. This study compares the C-scores of groups in the first and eighth semesters of study within each medical school and groups from corresponding semesters between the two medical schools. This study also evaluates the influence of such factors as age and gender on moral competence. A regression of moral judgment competence among the students in their eighth semester versus the students in the first semester of Brazilian medical school (p < 0.001) and a stagnation of moral competence among students in their eighth semester versus the first semester students in the Portuguese medical school (p = 0.06) were observed. For both the first semester and eighth semester groups, the students in the Portuguese medical school had higher C-scores than the students in the Brazilian medical school. In the analysis of the students' performances in terms of MJT dilemmas, the phenomenon of moral segmentation was observed in all of the groups, and the students performed better on the worker's dilemma than on the doctor's dilemma. Among students in the same semester of study, older students had lower C-scores. There was generally no significant difference between men's and women's C-scores. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Medical education; Medical students; Moral development; Moral judgment competence; Moral judgment test; Undergraduate medical education